Supervising Success: Strategies for Supporting Fast-track Postgraduate Students in Indonesia - Hari Setyowibowo; Nur Izzah, Nisrina; Juniarti Duwi Lestari; Asep Khoerudin; Harinaldi; Nuri Andar Wulan (HUMANITAS published by Universitas Ahmad Dahlan., 2024)
Students in fast-track postgraduate programmes face unique challenges, including intense academic pressure, role management difficulties, and high expectations for research output. This study, using the Self-Determination Theory (SDT) framework, specifically investigated good practices of supervisory strategies to improve postgraduate student well-being and academic performance in such accelerated programs. We collected data through online Focus Group Discussions (FGDs) with 264 supervisors from various academic fields and then analysed the data using thematic analysis. We incorporated expert review, FGDs facilitator guidance, and rigorous data validation processes to ensure trustworthiness. The findings reveal several critical challenges students face, including academic, self-management, relationship, financial, and program-related difficulties, highlighting areas where enhanced supervisory support is crucial. Furthermore, we found that supervisors assist students by providing essential academic information, offering structured guidance, and fostering a supportive environment. These findings can guide improved supervision strategies in a postgraduate fast-track programme.